2001
DOI: 10.1136/pmj.77.905.185
|View full text |Cite
|
Sign up to set email alerts
|

Cervical tuberculous lymphadenopathy: changing clinical pattern and concepts in management

Abstract: Tuberculosis is one of the biggest health challenges the world is facing. In this study the clinical pattern of patients with cervical lymphadenitis, who presented to the ear, nose, and throat outpatient department of the Government Medical College Hospital, Chandigarh, India between June 1997 and May 1998 is recorded. Tuberculosis accounted for 60 out of 94 cases of cervical lymph node enlargement. The commonest age group aVected was 11-20 years. Constitutional symptoms were not present in most of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
104
8
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(172 citation statements)
references
References 13 publications
30
104
8
19
Order By: Relevance
“…Nodal TB presenting as matted or sinuses has been discussed in many previous studies [5,19,20], however, in contrast to these studies, we found very few patients with presenting with these signs. Matted nodes were seen only in 17 (22.9 %) patients and sinus was seen in only one patient, who did not respond to treatment, and was later diagnosed to have MDR TB.…”
Section: Changing Trends In Presentation Of Cervical Nodes Of Tubercucontrasting
confidence: 89%
See 2 more Smart Citations
“…Nodal TB presenting as matted or sinuses has been discussed in many previous studies [5,19,20], however, in contrast to these studies, we found very few patients with presenting with these signs. Matted nodes were seen only in 17 (22.9 %) patients and sinus was seen in only one patient, who did not respond to treatment, and was later diagnosed to have MDR TB.…”
Section: Changing Trends In Presentation Of Cervical Nodes Of Tubercucontrasting
confidence: 89%
“…Our study shows a significant association between those with cervical node TB and having a history of contact with a patient already having TB (p \ 0.001). Studies on constitutional symptoms of cervical node TB show a wide variability [2,5]. These constitutional symptoms mimic other conditions with cervical node and cannot be attributed solely to TB.…”
Section: Size and Associated Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Cervical tuberculous lymphadenitis may represent a spread from the primary focus of infection in the tonsils. [9,10] Axillary tuberculous lymphadenitis is rare and has major prevalence between 20 and 50 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical lymph nodes constitute the most common site of involvement with axillary nodes affected in 3. [8][9][10][11][12][13][14][15][16][17][18][19][20].3% of tuberculous lymphadenitis [1,2]. Isolated axillary tuberculous lymphadenitis is rare and described in patients without previous or active pulmonary TB and no evidence of the origin of TB detected elsewhere [3,4].…”
Section: Introductionmentioning
confidence: 99%